Grains Word Search - Isabel Valentin-Oquendo; Claudia Peñuela (EDIS)
Search for foods from the Grain Group in the word search below. Some of these grains may be new to you, but try looking for them in the supermarket and then try a new recipe. Maybe you will find a new favorite! This revised 1-page fact sheet was written by Isabel Valentín-Oquendo and Claudia Peñuela and published by the UF Department of Family Youth and Community Sciences, April 2011.